Agronomic value of using deep-litter compost in lettuce cultivation (FAVE Sección Ciencias Agrarias, 2025)
The use of swine deep-litter waste (CCP) in horticulture contributes to the circular economy. This study evaluated the effect of CCP on soil organic matter (MOS), microbial biomass carbon (CBM), enzyme activity (FDA), aggregate stability (EA
Keywords: soil quality; horticulture; organic amendment; sustainable agriculture